Ocean Currents Drove Genetic Structure of Seven Dominant Mangrove Species Along the Coastlines of Southern China - Geng, Qifang; Wang, Zhongsheng; Tao, Jianmin; Kimura, Megumi K.; Liu, Hong; Hogetsu, Taizo; Lian, Chunlan (Frontiers in Genetics, 2021)
Mangrove forest ecosystems, which provide important ecological resources for marine environments and human activities, are being destroyed worldwide at an alarming rate. The objective of our study was to use molecular data and analytical techniques to separate the effects of historical and contemporary processes on the distribution of mangroves and patterns of population genetic differentiation. Seven mangrove species (Acanthus ilicifolius, Aegiceras corniculatum, Avicennia marina, Bruguiera gymnorrhiza, Kandelia obovata, Lumnitzera racemosa, and Rhizophora stylosa), which are predominant along the coastlines of South China, were genotyped at nuclear and chloroplast SSR markers. We estimated historical and contemporary gene flow, the genetic diversity and population structure of seven mangroves in China. All of these seven species exhibited a few haplotypes, low levels of genetic diversity (HE = 0.160-0.361, with the exception for K. obovata) and high levels of inbreeding (FIS= 0.104-0.637), which may be due to their marginal geographical distribution, human-driven and natural stressors on habitat loss and fragmentation. The distribution patterns of haplotypes and population genetic structures of mangroves in China suggest historical connectivity between populations of mangroves over a large geographic area. In contrast, significant genetic differentiation [FST = 0.165-0.629 (nSSR); GST = 0.173-0.923 (cpSSR)] indicates that populations of mangroves are isolated from one another with low levels of contemporary gene flow among populations. Our results suggest that populations of mangroves were historically more widely inter-connected and have recently been isolated, likely through a combination of ocean currents and human activities. In addition, genetic admixture in Beibu Gulf populations and populations surrounding Hainan Island and southern mainland China were attributed to asymmetric gene flow along prevailing oceanic currents in China in historical times. Even ocean currents promote genetic exchanges among mangrove populations, which is still unable to offset the effects of natural and anthropogenic fragmentation. The recent isolation and lack of gene flow among populations of mangroves may affect their long-term survival along the coastlines of South China. Our study enhances the understanding of oceanic currents contributing to population connectivity, and the effects of anthropogenic and natural habitat fragmentation on mangroves, thereby informing future conservation efforts and seascape genetics towards mangroves.